Research on Educational Discipline based on Ecosystem Theory - Xue, Jingtian (Transactions on Social Science, Education and Humanities Research, 2023)
Education discipline is an indispensable component within the field of education, yet it faces numerous challenges in practical implementation. This paper, grounded in the ecosystem theory, delves into the interaction between various ecosystems and hierarchical levels in the process of educational discipline, ranging from microsystems to macrosystems. Recognizing the subjective nature of educational discipline and taking into account individual variations among students and educators, this study proposes optimization strategies for educational discipline within different ecological system levels, namely teachers, parents, schools, society, and the nation.